Recruitment as Employee Retention Determinant at PT Victory International Futures - Setiawan, Michelle Joe; Gulo, Yupiter (Jurnal Abdimas Sosial, Ekonomi, dan Teknologi, 2024)
This Independent Internship Report is a form of accountability by explaining the author's activities in the Independent Internship program. This Independent Internship Program was implemented at PT Victory International Futures. PT Victory International Futures is a company engaged in financial services and trading. This Independent Internship aims to prepare students to enter the world of work and improve their competencies and abilities. In this report, the entire internship program will be explained as a Recruitment Officer Intern, as well as explaining the relationship between recruitment and employee retention in the company. The duties of the Recruitment Officer Intern at PT Victory International Futures are to create job postings and screen CVs, and conduct screening interviews with candidates. This Independent Internship Program was carried out for 3 months. However, there was limited and less complex access in the company. It would be better if in the future more contributions can be made with wider and more complex access.